The difficulties of Online Speaking Classroom at the Second Grade Students of SMA Negeri 1 Wonomulyo During Covid-19 Pandemic - Reskiani, Annisa; Hamid, Radiah; Firman (FKIP Unismuh Makassar, 2020)
This research aimed to find out the difficulties of online speaking classroom especially in speaking fluency at the Second Grade Students of SMA Negeri 1 Wonomulyo during Covid-19 Pandemic.The research used Descriptive Qualitative Method. Data of the research were collected through observation and questionnaire (open-ended questionnaire). The sample of this research was the Second Grade Students of SMA Negeri 1 Wonomulyo which amounted to 15 students who meet the criteria was chosen by purposively.Based on the research findings, the researcher found that 7 (46.67%) students had difficulty speaking online especially during the Covid-19 pandemic due to lack of confidence, 6 (40.00%) students were difficult in online learning process because of diddn't understand the material taught by the teacher and afraid of making mistakes. However, it can be overcome by extend the hours of studied beyond the school day. Therefore based on these results, it is recommended to use Online Speaking at speaking classrom, especially in speaking fluency to create a learning space that is flexible and can be done anywere.